2021
DOI: 10.1002/ijc.33404
|View full text |Cite
|
Sign up to set email alerts
|

Targeting USP13‐mediated drug tolerance increases the efficacy of EGFR inhibition of mutant EGFR in non‐small cell lung cancer

Abstract: In non‐small cell lung cancer (NSCLC), activating mutations in the epidermal growth factor receptor (EGFR) induce sensitivity to EGFR tyrosine kinase inhibitors. Despite impressive clinical responses, patients ultimately relapse as a reservoir of drug‐tolerant cells persist, which ultimately leads to acquired resistance mechanisms. We performed an unbiased high‐throughput siRNA screen to identify proteins that abrogate the response of EGFR‐mutant NSCLC to EGFR‐targeted therapy. The deubiquitinase USP13 was a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…Remarkably, Spautin-1 5aa showed moderate EGFR TK inhibitory activity at the standard screening concentration ( Table 2 ), however we did not observe a reduction in pEGFR at 10 µM in EGFR mutant NSCLC cells [ 25 ]. We reasoned that the concentration used in the kinase screening does not represent the actual intracellular concentration upon treatment with the same concentration on a cellular basis.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Remarkably, Spautin-1 5aa showed moderate EGFR TK inhibitory activity at the standard screening concentration ( Table 2 ), however we did not observe a reduction in pEGFR at 10 µM in EGFR mutant NSCLC cells [ 25 ]. We reasoned that the concentration used in the kinase screening does not represent the actual intracellular concentration upon treatment with the same concentration on a cellular basis.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the differential role of USP13 in tumorigenesis, this enzyme is considered as a potential therapeutic target. Recently, we have reported that inhibition of USP13 destabilizes EGFR and that co-inhibition of USP13 and EGFR suppresses oncogenic signaling in NSCLC cells [ 25 ]. These findings motivated us to initiate the development of more potent USP13 inhibitors, starting from the only USP13 inhibitor described in the literature to date (Spautin-1, 5aa , Figure 2 ) [ 26 ], by exploring the chemical space around Spautin-1 and determining the importance of the quinazoline core by performing a “ N -screening”.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on DTCs in EGFR -mutated lung cancers that followed the discovery of Sharma et al [ 21 ] used short-term treatment with an EGFR TKI at clinically achievable concentrations to establish DTCs against EGFR TKIs (Figure 2A). As summarized in Section 4 , these studies have identified multiple molecular mechanisms of drug tolerance [ 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], although they do not identify the original cells that can become DTCs while the majority of cells are killed. These studies also do not answer the question of how these few cells can acquire specific molecular mechanism(s) of drug tolerance.…”
Section: Features Of Dtcsmentioning
confidence: 99%
“…While cancer cells may have a “preference” for drug tolerance mechanisms, it is also true that multiple drug tolerance mechanisms have been reported in each lung cancer cell line. For example, >10 drug tolerance mechanisms (involving IGF-1R, AXL, FGFR3, AURKA, STAT3, NF-kB, YAP/TEAD, and other mechanisms) are employed by PC9 cells [ 28 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 42 , 43 , 44 ]. This diversity may be partly explained by the properties of EGFR TKIs, differences in their concentrations, differences in TKI exposure times, or combinations of these experimental manipulations.…”
Section: Features Of Dtcsmentioning
confidence: 99%
See 1 more Smart Citation